The coins of Complutensian Polyglot Bible - de Francisco Olmos, José María (Revista General de Información y Documentación, 2013)
This paper studies the coin that was in circulation in Castile when Cardinal Cisneros founded Complutense University, the time when The Complutensian Polyglot Bible was accomplished. The coin value and typology is studied as well as the influence of foreign currency on Castilian accounts.
Keywords: The Complutensian Polyglot Bible; cardinal Cisneros; coins; Castile; Catholic Monarchs